PENGEMBANGAN SKEMATA AFEKSIDALAM PEMBELAJARAN - Jum Anidar (Jurnal Al-Taujih : Bingkai Bimbingan dan Konseling Islami, 2015)
Affective development is a process that consists of individual growth or internal changes to give the best attention of the individual and social. Affective is the end result of the process is done. While the development of affective education consists of the conscious and deliberate interventions to the development of learners, it includes sections of material or integrated in the curriculum or include a separate material to develop affection as a process and as an end result. The tendency of attitude becomes one of the considerations in the school for over a decade. Affective raised by a variety of different forms, including a humanistic education, moral development, learning centered on the learner, self-actualization, and the value of education, and other terms. Affective domain taxonomy levels according to Krathwohl there are five, namely: receiving (attending), responding, valuing, organization, and characterization. Strategies that can be used in developing this affection schemata is to adopt a scientific approach. The main steps that must be taken in a scientific approach are: Observing (Observing), ask (Questioning), Trying (experimenting), reasoning and Communicating.